Selective privatization of security: why American strategic leaders choose to substitute private security contractors for national military force - Stanley, Bruce Edwin (Kansas State University, 2012)
Ideas about why US foreign policy actors have turned ever more frequently to private military contractors (PMCs) and private security contractors (PSCs) over the past decade and a half abound. Descriptive accounts of the rise of these corporations have become something of a cottage industry over the past decade or so. The various ideas advanced have yet to be placed under rigorous empirical scrutiny, however. This dissertation builds from the existing descriptive literature to advance a new theoretical framework to explain the rise of private contractors. It analyzes this framework as well as alternative ideas using both quantitative and qualitative analysis, marking the first time this important subject has been systematically examined with both social science methods.
Keywords: Private; Contractors; Security; International Relations (0601); Military Studies (0750); Political Science (0615)